Supported and Coerced? A Cross-site Investigation of the Effects of Social Support and Coercion on Criminal Probability - Antonaccio, Olena (Journal of quantitative criminology, 2015)
Objectives We test several principal hypotheses regarding individual criminal behavior derived from the integrated theory of Differential Coercion/Social Support (DCSS). Methods We use random sample household survey data from 1,000 respondents in two major cities, one in Bangladesh and one in Ukraine. In our site-specific analyses, we examine bivariate associations to estimate relations between global and domain-specific social support and coercion. We use negative binomial regressions with robust standard errors to assess separate, simultaneous, and interactive effects of social support and coercion on criminal probability, and, where appropriate, mediating effects of self-control and anger. Results Consistent with the theory, coercion and social support are found to be independent rather than being opposite ends of a single continuum, although their inverse relationship is found to be substantially weaker than the theory implies. The data also support the idea that coercion has a crime generative effect, although they provide little confirmation of hypotheses about social support and criminal probability or about social support’s interrelationship with coercion. The results do suggest that beneficial effects of social support may be more pronounced and detrimental effects of coercion weakened in the more supportive context of Bangladesh, suggesting that their effects are sensitive to macro-level socio-cultural influences. Furthermore, the effects of both social support and coercion vary across different life domains. Finally, the results provide partial support for mediation hypotheses, with anger and sometimes self-control emerging as significant mediators of relationships between coercion and violence in the Ukrainian sample. Conclusions Our findings highlight the explanatory potential of DCSS, though the coercion part of the theory appears to be more viable than the social support part. The results suggest specific areas where theoretical refinement and clarification are needed, and they point toward some important policy implications.